TOWN AND COUNTRY IN ROMAN BRITAIN - Rivet, A. L. F. (Albert Lionel Frederick), 1915- Link ([S.l.])
1 online resource
Keywords: Town and Country in Roman Britain (1964) is a study of the effects of Roman rule on the lowland zone of Britain and of the relationship between town and country. The author places the Romano-British towns and villas in their economic and political setting, and discusses their origin and development with the aid of current scholarship and archaeological evidence.